Methanol as carbon substrate in the bio‐economy: Metabolic engineering of aerobic methylotrophic bacteria for production of value‐added chemicals. (9th May 2017) - Pfeifenschneider, Johannes; Brautaset, Trygve; Wendisch, Volker F.
Abstract: Bacteria are widely used as cell factories for production of enzymes and chemicals, mostly from sugars. Methylotrophic bacteria can utilize the one‐carbon compound methanol as sole carbon source for growth, and metabolic engineering is being used to develop bioprocesses based on these organisms for conversion of methanol into value‐added chemicals. Methylotrophic model strains include both Gram‐positive and Gram‐negative bacteria and in all cases methanol metabolism proceeds via the cell‐toxic intermediate formaldehyde. Thus, understanding the genetics, biochemistry, and regulation of methylotrophic pathways is crucial for successful strain development and for their concomitant fermentations. Also, such basic knowledge has proven useful for design of strategies and approaches for the rational transfer of methylotrophy into non‐methylotrophic bacteria. In the current review we highlight the best studied methylotrophic model organisms, with particular focus on the Gram‐positive Bacillus methanolicus and the Gram‐negative Methylobacterium extorquens, including their genetics and physiology. We present successful metabolic engineering examples leading to the construction of recombinant strains for the production of amino acids, platform chemicals, terpenoids and dicarboxylic acids derivatives from methanol as sole carbon source. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd